Ciencia e investigación agraria 2018
DOI: 10.7764/rcia.v45i3.1886
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid, mineral, condensed tannin, and other chemical contents of olive leaves (Olea europaea L.) processed via solid-state fermentation using selected Aspergillus niger strains

Abstract: Altop, I. Coskun, G. Filik, A. Kucukgul, Y.G. Bekiroglu, H. Cayan, E. Gungor, A. Sahin and G. Erener. 2018. Amino acids, minerals, condensed tannin, and other chemical contents in olive leaves (Olea europaea L.) processed via solid-state fermentation using selected Aspergillus niger strains. Cien. Inv. Agr. 45(3): 220-230.The present study aimed to examine the effects of solid-state fermentation (SSF) using selective A. niger strains on the amino acid, mineral, condensed tannin, and other chemical contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…In this study, the crude ash content was increased, however, the reason for the increase is not known precisely because no mineral substance analysis was performed. As a result of fermentation of industrial by-products with bacteria, yeast and fungi, it has been determined that the content of crude fat increases by 20-50% (Joshi and Devender, 2006;Madrera et al, 2017;Altop et al, 2018). Similar results were obtained from previous studies of P. ostreatus fermentation.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, the crude ash content was increased, however, the reason for the increase is not known precisely because no mineral substance analysis was performed. As a result of fermentation of industrial by-products with bacteria, yeast and fungi, it has been determined that the content of crude fat increases by 20-50% (Joshi and Devender, 2006;Madrera et al, 2017;Altop et al, 2018). Similar results were obtained from previous studies of P. ostreatus fermentation.…”
Section: Resultssupporting
confidence: 69%
“…There are many studies reporting decreased crude fibre and its fractions by the solid-state fermentation (Lateef et al, 2008;Yasar and Tosun, 2018c;Karakurt et al, 2019). Altop et al (2018) reported that the starch and sugar content of industrial by-products were reduced as a result of fungal fermentation. In our study, P. ostreatus and P. chrysosporium microorganism fermentation significantly decreased crude fibre, ADF, NDF and reducing sugar, similar to previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Solid-state fermentation increases radical scavenging activity by raising the amount and/or effectiveness of phenolic compounds in the fermentation medium [ 34 ]. However, A. niger can use some phenolic compounds as a carbon source during fermentation [ 35 ]. A reduction in the radical scavenging activity of GP can be due to A. niger consuming phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, solid-state fermentation has been an effective tool for recycling agro-industrial residues in useful animal feeds. Solid-state fermentation has improved the nutritional composition of shea nut (Dei et al, 2008 ), cottonseed meal (Jazi et al, 2017 ), pine needle (Wu et al, 2015 ), olive leaves (Altop et al, 2018 ), and sweet cherry ( Prunus avium L.) kernel (Altop, 2019 ). Aspergillus niger can produce various enzymes, such as protease, amylase, lipase, cellulase, and tannase (Couri et al, 2000 ; Wu et al, 2015 ), and also decrease antinutritional components in Ginkgo biloba leaves (Zhang et al, 2012 ), cottonseed meal (Jazi et al, 2017 ), and olive leaves (Xie et al, 2016 ) with solid-state fermentation.…”
Section: Introductionmentioning
confidence: 99%